Profile of epilepsy in a tertiary care public sector hospital of western India - Gupta, Anuj; Desai, Chetna (International Journal Of Community Medicine And Public Health, 2017)
Background: Epilepsy is characterised by recurrent seizures due to a chronic underlying process. Its prevalence in India is 6.24/1000 population. The study aims to evaluate the commonest types of and clinical characteristics of epilepsy, and pharmacological management in these patients. Furthermore to assess, whether these variables are in agreement with other local and international studies? Methods: This cross-sectional observational study was carried out in an epilepsy clinic of a public sector hospital in India for a period of nine months. The study analysed medical records of patients during the study period. Simple descriptive statistical tests (Mean and Standard deviation) were used to describe the numerical values of the sample while qualitative data were presented by frequency distribution. Results: A total 297 patients were enrolled, after informed consent. The male: female ratio was 1.94. The age ranged between six months and 12 years (mean±SD =6.2±2.9). Majority of patients had generalised tonic-clonic seizure (71.71%), followed by complex partial seizure (12.79%). 70.03% of our patients had idiopathic epilepsy. The commonest causes for symptomatic epilepsy were hypoxic ischaemic insult and CNS infections. Mental retardation and cerebral palsy were common comorbidities. Sodium valproate was the most commonly prescribed drug and 75.08% patients were on monotherapy. Conclusions: Seizure types, aetiology, drug therapy, comorbidities and outcome in a tertiary care hospital in India are similar to previous local and international studies. Preventable causes of epilepsy share a significant portion in the aetiology of the disease. Sodium valproate was seen to have more promising results in paediatric patients for generalized tonic clonic seizure.